Evaluation of Indoor Air Quality in Laboratory Rooms at Poltekkes Riau Based on the Indonesian Ministry of Health Regulation No. 48 of 2016 - Nopriandi, Nopriandi; Zulherman; I Nengah Tela (RUSTIC, 2025)
Indoor air quality (IAQ) in educational laboratories is critical for safeguarding occupant health and structural integrity. Elevated CO₂ levels (>1,000 ppm) impair cognitive function and cause drowsiness, while formaldehyde (HCHO) emissions from building materials are carcinogenic (Group 1 IARC) and trigger respiratory inflammation. Total Volatile Organic Compounds (TVOCs) induce sick building syndrome through chronic exposure, damaging neurological and hepatic systems. Particulate matter poses multifaceted threats: PM₁₀ deposits in upper airways causing irritation, PM₂.₅ penetrates lung alveoli increasing cardiovascular mortality risk (WHO, 2021), and PM₁.₀ translocates to bloodstream carrying adsorbed toxins. Beyond health impacts, these pollutants degrade building systems—PM accumulation corrodes HVAC components, HCHO embrittles organic materials, and TVOCs form surface films that accelerate wear. This study quantitatively assessed IAQ in ten Poltekkes Riau laboratories against Indonesian Ministry of Health Regulation No. 48/2016 thresholds. Real-time measurements of CO₂, HCHO, TVOC, and particulate fractions (PM₁.₀/PM₂.₅/PM₁₀) were conducted under active/inactive ventilation modes. Results revealed widespread noncompliance: 80% of labs exceeded PM₂.₅/PM₁₀ limits during ventilation downtime, while microbiology and health promotion labs showed hazardous TVOC (max 1,200 µg/m³) and HCHO (max 120 ppb) concentrations. These findings demonstrate systemic IAQ failures, necessitating urgent ventilation upgrades and low-emission material retrofits to mitigate health risks and preserve building functionality.